Reinterpretasi "Sajak Anak Muda" Karya W.S.Rendra dalam Pementasan Lintasmedia - Mukafi, Muhammad Hamdan; Al Faqih, Dinar Rizqy (Sabda: Jurnal Kajian Kebudayaan, 2023)
Literature is not always related to aesthetic texts only. In fact, literary texts are capable of transformation as a reinterpretation process is carried out on a work, such as the process of reinterpretation of a work, such as the performances that inspired the poem "Sajak Anak Muda" written by by W.S. Rendra. As a poet, Rendra has already interpreted the poem in the form of performance of his poem. Because of the ability of the poem to an era beyond the time it was written, it is not surprising that Emhaf and Gazebo Theater also reinterpreted and created new nuances to the poem. The new nuances that are present are questioned as a reception that is realized in the form of a theatrical performance. Furthermore, the ability of reception that presents a new interpretation is also examined to what extent it is able to be present in the space and time of the poem. Also, to what extent it is able to exist in a time and space that exceeds the time when the poem was written. Thus, a continuous effect is born that looks at how the poem is perceived. Emhaf and Gazebo Theater re-represent the educational context that developed from the poem of the poem "Sajak Anak Muda" by W.S. Rendra.Sastra tidak selalu berkaitan dengan teks estetik saja. Nyatanya, teks sastra mampu bertransformasi sebagaimana proses reinterpretasi dilakukan terhadap suatu karya, seperti pertunjukan-pertunjukan yang mengilhami puisi “Sajak Anak Muda” yang ditulis oleh W.S. Rendra. Sebagai penyair, Rendra sudah pernah melakukan interpretasi dalam bentuk pementasan terhadap puisi karyanya tersebut. Oleh sebab kemampuan puisi tersebut untuk pada zaman yang melebihi waktu ditulisnya, tidak mengherankan apabila Emhaf dan Teater Gazebo pun melakukan reinterpretasi dan menciptakan nuansa baru terhadap puisi tersebut. Nuansa baru yang hadir dipersoalkan sebagai resepsi yang diwujudkan dalam bentuk pementasan teaterikal. Lebih lanjut, kemampuan meresepsi yang menghadirkan interpretasi baru itu pun dikaji sejauhmana mampu hadir dalam ruang dan waktu yang melebihi zaman ketika puisi tersebut ditulis. Hingga lahirlah efek yang berkesinambungan melihat bagaimana Emhaf dan Teater Gazebo merepresentasikank embali konteks pendidikan yang berkembang dari puisi “Sajak Anak Muda” karya W.S. Rendra.